Assessment of the Role of Ginsenoside RB1 Active Substance in Alginate/Chitosan/Lovastatin Composite Films. (7th April 2020) - Thach, Thi-Loc; Nguyen, Thuy-Chinh; Vo, An-Quan; Do, Minh-Thanh; Nguyen, Quang-Tung; Nguyen, Tuan-Anh; Bach, Long-Giang; Thai, Hoang
Abstract : This article reports the effect of ginsenoside Rb1 on some properties, morphology, and the drug release process of the chitosan (CS)/alginate (AG)/lovastatin (LOV) composite films prepared by a solution method using different contents of ginsenoside Rb1. The ratio of AG/CS was fixed at 4/1 (wt.%/wt.%), the content of LOV was 10 wt.%, and the content of ginsenoside Rb1 was changed from 1 to 5 wt.%. The results of scanning electron microscopy and Fourier transform infrared spectroscopy analysis showed that the composite films have a heterogeneous structure and the ginsenoside Rb1 content influenced on the structure of composite films. The presence of ginsenoside Rb1 did not influence on the melting temperature of these films but caused a significant difference in the melting enthalpy of the films. The ginsenoside Rb1 was also contributed positively on the LOV release from these films in different pH buffer solutions. The LOV release process from these films included two stages (fast/burst release and slow/control release). It was increased remarkably by the synergic effect of LOV and ginsenoside Rb1 in the drug release process. From the obtained results, we suggested that ginsenoside Rb1 plays an important role not only in the enhancement of health and immunity as general but also as an efficient agent in control of the LOV size as well as LOV drug release from the composite films.